Mutational Analysis of a Conserved Glutamic Acid Required for Self-Catalyzed Cross-Linking of Bacteriophage HK97 Capsids - Dierkes, Lindsay E. (American Society for Microbiology (ASM), 2009)
The capsid of bacteriophage HK97 is stabilized by ∼400 covalent cross-links between subunits which form without any action by external enzymes or cofactors. Cross-linking only occurs in fully assembled particles after large-scale structural changes bring together side chains from three subunits at each cross-linking site. Isopeptide cross-links form between asparagine and lysine side chains on two subunits. The carboxylate of glutamic acid 363 (E363) from a third subunit is found ∼2.4 Å from the isopeptide bond in the partly hydrophobic pocket that contains the cross-link. It was previously reported without supporting data that changing E363 to alanine abolishes cross-linking, suggesting that E363 plays a role in cross-linking. This alanine mutant and six additional substitutions for E363 were fully characterized and the proheads produced by the mutants were tested for their ability to cross-link under a variety of conditions. Aspartic acid and histidine substitutions supported cross-linking to a significant extent, while alanine, asparagine, glutamine, and tyrosine did not, suggesting that residue 363 acts as a proton acceptor during cross-linking. These results support a chemical mechanism, not yet fully tested, that incorporates this suggestion, as well as features of the structure at the cross-link site. The chemically identical isopeptide bonds recently documented in bacterial pili have a strikingly similar chemical geometry at their cross-linking sites, suggesting a common chemical mechanism with the phage protein, but the completely different structures and folds of the two proteins argues that the phage capsid and bacterial pilus proteins have achieved shared cross-linking chemistry by convergent evolution.